2012
DOI: 10.1039/c1mb05100h
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic RNA partitioning generates transient increases in the normalized variance of RNA numbers in synchronized populations of Escherichia coli

Abstract: We explore the effects of probabilistic RNA partitioning during cell division on the normalized variance of RNA numbers across generations of bacterial populations. We first characterize these effects in model cell populations, where gene expression is modeled as a delayed stochastic process, as a function of the synchrony in cell division, the rate of division, and the RNA degradation rate. We further explore the additional variance that arises if the partitioning is biased. Next, in Escherichia coli cells ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(40 reference statements)
0
12
1
Order By: Relevance
“…Genome-wide assessments of cell-to-cell diversity in RNA numbers suggest otherwise [16]. However, these results depend not only on the kinetics of transcription but also on the kinetics of RNA degradation [8] and RNA partitioning in cell division [32,33], while our results do not.…”
Section: Discussioncontrasting
confidence: 65%
“…Genome-wide assessments of cell-to-cell diversity in RNA numbers suggest otherwise [16]. However, these results depend not only on the kinetics of transcription but also on the kinetics of RNA degradation [8] and RNA partitioning in cell division [32,33], while our results do not.…”
Section: Discussioncontrasting
confidence: 65%
“…Other studies have shown that RNA production in bacteria is a stochastic (24,69) and a multi-step process (30), generally subject to complex regulatory mechanisms (8). Finally, recent studies have shown that the cell-to-cell diversity in RNA numbers, and likely protein numbers, can be significantly affected by processes other than gene expression (47,48,51). Therefore, the assessment of the kinetics of gene expression and regulation requires in vivo measurements of RNA production dynamics in individual cells, one event at a time, under various induction and environmental conditions (40).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the RNA molecules are partitioned in an unbiased fashion, the stochastic nature of this process will enhance the cell-to-cell diversity in the numbers of these molecules following division events (47,48). In addition, bacteria are known to partition unwanted protein aggregates in a biased fashion (49,50), including, for example, RNA tagged with MS2 coat protein fused with Green Fluorescent Protein (MS2-GFP) (51,52), and fluorescent proteins such as Tsr-Venus (53,54,55). This bias in partitioning ought to exacerbate cell-to-cell diversity in RNA and protein numbers when assessed by these methods.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques have allowed uncovering the transcription kinetics of promoter systems in E. coli at the single-cell level (Kandhavelu et al, 2011; So et al, 2011; Lloyd-Price et al, 2012; Muthukrishnan et al, 2012; Iyer et al, 2016; Sepulveda et al, 2016) and led to the acknowledgment that various mRNAs are in fact localized in different ways in bacterial cells (Nevo-Dinur et al, 2011; dos Santos et al, 2012; Moffitt et al, 2016). The systems that were used to enable these pioneering studies are now gradually being replaced by more accurate, less invasive techniques.…”
Section: Resultsmentioning
confidence: 99%